Avaliação da estabilidade hidráulica de diques homogêneos de enrocamento galgáveis utilizando modelo físico reduzido - Livia Jacobini (2019)
Overtopped rockfill dams are drainage structures, generally used to contain mining sediments. These structures have a lowering in the central portion of the body of dam for flooding. The spillway is incorporated into the dam. Generally these dams are constructed with 3 m to 15 m of height, and softer downstream slope, approximately 3,0 to 6,0 H: 1,0 V. In Brazil, there are few studies related to this topic, and recent international studies on rockfill dams are more directed to studies of structures with the possibility of overtopping, and not to the case in which the overtopping occurs during the passage of any flood. In this context, in this dissertation the hydraulic performance of overtopped homogeneous embankment dam was investigated, regarding the stability of the blocks, by means of a scaled physical model, determining the seepage flow through the blocks and the maximum value of specific flow (flow rate per unit of surface width of the spillway) over that there is no damage to the structure in blocks, considering the continuous overtopping during the whole operational life of the dam. The tests were carried out in two channels at the Hydraulic Research Center (CPH) in Federal University of Minas Gerais (UFMG), one on a smaller scale, to define the test methodology and to mitigate the mishaps, and later the tests were performed in a channel with larger dimensions, allowing to evaluate the effect of scale between the models. From the concept of forces balance in the particle proposed by Shields, the force diagram for the dam situation was carried out and an equation and graphs were proposed to evaluate the stability of overtopped rockfill dams. It was verified that the stability of the dam is related to the specific weight and friction angle of the rockfill particle, downstream slope and slope of the hydraulic head in the dam. The results obtained were converted into prototype for use in dam design situations with typical geometry of structures of this nature, using the similarity by Froude number.